PENINGKATAN KETERAMPILAN MEMBACA PEMAHAMAN DENGAN MENGGUNAKAN METODE SUSTAINED SILENT READING SISWA SEKOLAH DASAR - Rheinanda Nabilla Putri Maidy; Putri Hana Pebriana; Iis Aprinawati; Sumianto; Fadhilaturrahmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The background of this research is the low reading comprehension skills of students in grade 5. This research aims to improve the reading comprehension skills of grade 5 students at SDN 005 Binuang. This research is a classroom action research (CAR), which is carried out in two cycles and each cycle consists of two meetings. The subjects in this study were all 15 grade 5 students. Data collection techniques were in the form of interviews, observations, documentation and tests. While the data analysis technique used was a combination of qualitative and quantitative. Based on the results of the research that has been carried out through 2 cycles, at the first meeting of cycle 1 there were 5 students who completed the reading comprehension with a percentage of 33.33% and at the second meeting it increased to 7 students with a percentage of 46.67%. While in the second meeting of cycle 1 there were 9 students who completed the reading comprehension with a percentage of 60% and there was an increase at the second meeting to 13 people with a percentage of 86,67%. Based on the results of this study, it shows that by applying the SSR learning technique it can improve the reading comprehension of grade 5 students at SDN 005 Binuang.